Stanovení nejistoty měření souřadnicového měřicího stroje v nanometrologii - Potanko, Andrej (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2022)
Diplomová práca rieši problematiku stanovenia neistoty merania na súradnicových meracích strojoch v oblasti nanometrológie. Jedná sa o stroje SIOS NMM 1 a Zeiss UPMC 850 Carat, ktoré sa využívajú na pracovisku ČMI v Brne. V teoretickej časti je práca venovaná základnej terminológii v oblasti merania a obecnej charakteristike súradnicových meracích strojov. Teoretickú časť uzatvára popis prístrojov použitých k meraniu. V praktickej časti sú realizované experimentálne merania na obidvoch prístrojoch s následným identifikovaním a kvantifikovaním jednotlivých zložiek neistôt ovplyvňujúcich výsledok merania. Posledná časť práce je venovaná celkovému vyhodnoteniu merania na prístrojoch Zeiss a SIOS a ich metrologickému porovnaniu.

The diploma thesis deals with the determination of measurement uncertainty on coordinate measuring machines in the field of nanometrology. These are SIOS NMM 1 and Zeiss UPMC 850 Carat machines, which are used at the CMI workplace in Brno. In the theoretical part, the work is devoted to basic terminology in the field of measurement and general characteristics of coordinate measuring machines. The theoretical part concludes with a description of the devices used for measurement. In the practical part, experimental measurements are performed on both devices with subsequent identification and quantification of individual components of uncertainties affecting the measurement. The last part of the thesis is devoted to the overall evaluation of measurements on Zeiss and SIOS devices and their metrological comparison.
Determination of measurement uncertainty of a coordinate measuring machine in nanometrology
Keywords: Súradnicové meracie stroje; experimentálne meranie; neistota merania; SIOS NMM-1; Zeiss UPMC 850 Carat; Coordinate measuring machines; experimental measurement; uncertainty of measurement; SIOS NMM-1; Zeiss UPMC 850 Carat